Mengatasi Keterbatasan SWOT Permukaan melalui Model SWOT–Iceberg: Pendekatan Analisis Struktur Tersembunyi untuk Formulasi Strategi Organisasi yang Berkelanjutan - Ramadhani, Nia; Regina, Nashwa Deninta; Lestari, Amri Khoirika Puji; Siswanto, Ali Hasan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
SWOT analysis has long been used in organizational strategy formulation, but this approach is considered inadequate because it focuses only on surface symptoms and ignores hidden factors such as culture, assumptions, and mindsets that influence the formation of strengths, weaknesses, opportunities, and threats. This study aims to: (1) critique the limitations of traditional SWOT as a strategic analysis tool; (2) integrate the Iceberg Model to reveal the deepest structures that influence SWOT variables; and (3) formulate a conceptual SWOT–Iceberg model as a sustainable strategic solution for modern organizations. The method used is a qualitative-conceptual approach with a systematic literature review, covering Scopus/WoS articles from 2015–2025 related to SWOT, systems thinking, mental models, and organizational strategy. The data were analyzed through thematic coding and conceptual synthesis and validated using expert judgment from strategic management experts. The results show that 80% of the determinants of organizational strategy are at the bottom of the iceberg—namely, policy systems, power structures, values, and collective assumptions—which have not been accommodated in SWOT. Therefore, the SWOT–Iceberg Framework model was developed, which repositions SWOT into four layers of analysis: events, patterns, systemic structures, and mental models. In conclusion, the SWOT–Iceberg model offers a paradigm shift from descriptive SWOT to a reflective-strategic tool that can uncover the root causes of problems and produce more adaptive and sustainable strategies. Further research is recommended to empirically test this model in educational institutions, digital businesses, or public institutions.